Resveratrol inhibits growth of orthotopic pancreatic tumors through activation of FOXO transcription factors. - Sanjit K Roy; Qinghe Chen; Junsheng Fu; Sharmila Shankar; Rakesh K Srivastava (PLoS ONE, 2011)
BACKGROUND: The forkhead transcription factors of the O class (FOXO) play a direct role in cellular proliferation, oxidative stress response, and tumorigenesis. The objectives of this study were to examine whether FOXOs regulate antitumor activities of resveratrol in pancreatic cancer cells in vitro and in vivo. METHODOLOGY/PRINCIPAL FINDINGS: Pancreatic cancer cell lines were treated with resveratrol. Cell viability, colony formation, apoptosis and cell cycle were measured by XTT, soft agar, TUNEL and flow cytometry assays, respectively. FOXO nuclear translocation, DNA binding and transcriptional activities were measured by fluorescence technique, gelshift and luciferase assay, respectively. Mice were orthotopically implanted with PANC1 cells and orally gavaged with resveratrol. The components of PI3K and ERK pathways, FOXOs and their target gene expressions were measured by the Western blot analysis. Resveratrol inhibited cell viability and colony formations, and induced apoptosis through caspase-3 activation in four pancreatic cancer cell lines (PANC-1, MIA PaCa-2, Hs766T, and AsPC-1). Resveratrol induced cell cycle arrest by up-regulating the expression of p21/CIP1, p27/KIP1 and inhibiting the expression of cyclin D1. Resveratrol induced apoptosis by up-regulating Bim and activating caspase-3. Resveratrol inhibited phosphorylation of FOXOs, and enhanced their nuclear translocation, FOXO-DNA binding and transcriptional activities. The inhibition of PI3K/AKT and MEK/ERK pathways induced FOXO transcriptional activity and apoptosis. Furthermore, deletion of FOXO genes abrogated resveratrol-induced cell cycle arrest and apoptosis. Finally, resveratrol-treated mice showed significant inhibition in tumor growth which was associated with reduced phosphorylation of ERK, PI3K, AKT, FOXO1 and FOXO3a, and induction of apoptosis and FOXO target genes. CONCLUSIONS: These data suggest that inhibition of ERK and AKT pathways act together to activate FOXO transcription factors which are involved in resveratrol-mediated pancreatic tumor growth suppression.